Student engagement in K12 online education during the pandemic: The case of Turkey - KURT TİFTİK, GÖKÇE (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Student engagement has become a challenge for K-12 students and teachers in online education during the COVID-19 pandemic. This study explored the factors underlying student engagement and the strategies teachers developed to engage students. Thematically analyzed interview data coming from 22 teachers and 20 students of public high schools revealed teachers' and students' similar perceptions of the factors affecting student engagement. The four themes identified were instructional and student related factors along with those related to the learning environment and policies. The teacher strategies for the facilitation of student engagement were instructional, managerial, and affective. Teachers also discussed which of these strategies were helpful in fostering student engagement.
Keywords: Student engagement; K-12; online education; teacher strategies; pandemic; ACADEMIC-ACHIEVEMENT; SCHOOL ENGAGEMENT; GROUP-SIZE; DISTANCE; PARTICIPATION; DISENGAGEMENT; SATISFACTION; PERCEPTIONS; PERFORMANCE; TECHNOLOGY